Electrochemical synthesis of graphene quantum dots from graphene oxide at room temperature and its soil moisture sensing properties. (15th September 2020) - Kalita, Hemen; Palaparthy, Vinay S.; Baghini, Maryam Shojaei; Aslam, M.
Abstract: Graphene quantum dots (GQDs) the quantum dot variety of graphene represent a new group of quantum dots with exciting properties. Herein we report the electrochemical synthesis of GQDs with size ranging from 3 to 5 nm in diameter from graphene oxide (GO) at room temperature with LiClO4 in propylene carbonate as the electrolyte. The size of the GQDs can be tuned by playing with different parameters such as the applied potential, oxidation and reduction time, concentration of the supporting electrolyte. GQDs are promising candidate for humidity sensors, chemical sensors, nanoelectronic devices and biomarkers. In this paper, the potential use of the GQD as soil moisture sensors is also explored. We fabricated the micro-sensor where GQDs is used as the sensing material to perform the soil moisture measurements on two different soils. In our study, we observed that when soil water content varies from 0% to 32%, then sensor resistance changes by 99% and 97% for the red soil (silt loam) and black soil (clayey), respectively. We found that sensor response time was around 180 s for the both silt loam and clayey soils. Graphical abstract: Image 1 Highlights: Graphene quantum dots (GQDs) is synthesized from graphene oxide by electrochemical method. The method is a room temperature synthesis process with control over the size of the GQDs. Micro-sensor is fabricated and the soil moisture sensing properties of the GQDs on two different soil types are studied. The passivated GQDs sensor is compared with the as-prepared GQDs sensor. The sensing mechanism is explained by the H-bonding between GQDs and water molecules.